INSOMNIA AND CORRELATION WITH PSYCHOSOCIAL FACTORS IN PRIMARY HEALTH CARE - Cahyadi Permana, Made Gede (E-Jurnal Medika Udayana, 2013)
Insomnia is regarded as sleep disorder that most often affects people in the world, both in primary and in the presence of comorbid conditions. Based on those facts, insomnia could be a serious problem at the level of primary health care. General Practitioner should be able to diagnose insomnia and able to perform the appropriate treatment for the patient. Psychosocial factors may related to the degree of severity of insomnia, among others are health status, depression, dysfunctional beliefs of sleep, self efficacy, and demographic. By knowing the relationship between psychosocial factors and insomnia, General practitioners are expected to create a holistic pattern of management of insomnia.
Keywords: Insomnia, psychosocial factors